In vitro efficacy of antifungal agents alone and in shampoo formulation against dandruff‐associated Malassezia spp. and Staphylococcus spp. (9th May 2019) - Leong, C.; Schmid, B.; Buttafuoco, A.; Glatz, M.; Bosshard, P. P.
Abstract: Objective: Dandruff is a complex skin condition characterized by unpleasant itching and flaking of the scalp. It is primarily attributed to the over colonization of Malassezia yeasts such as Malassezia globosa and Malassezia restricta . Some studies also suggest the involvement of staphylococci bacteria in dandruff disease pathogenesis. We aimed to access the effectiveness of anti‐dandruff treatments by determining the efficacy of the active antifungal agents alone or in commercial shampoo formulations against Malassezia and Staphylococcus . Methods: The minimum inhibitory concentrations of three anti‐dandruff shampoo antifungals (zinc pyrithione, ketoconazole and ciclopirox) and the witch hazel extract, hamamelitannin were tested against commensal Malassezia and Staphylococcus species using broth microdilution methods. In experiments simulating shampoo exposure and washing conditions on the scalp, we also tested the ability of the above agents in shampoo formulation (Head and Shoulders ® (H&S), Ketomed ®, Sebiprox ®, Erol Healthcare Hair Shampoo ® respectively) along with a generic over‐the‐shelf shampoo to inhibit microbial growth. Results: Ketomed ® and H&S shampoo were the most effective treatments against Malassezia in in vitro assays and washing simulation experiments. Erol Healthcare Hair Shampoo ® was less effective against Malassezia as it required a longer contact time to achieve growth inhibition for some species. Sebiprox ® showed variable efficacy in washing and contact time experiments whereas the generic over‐the‐shelf shampoo was the least effective in inhibiting Malassezia and Staphylococcus growth. Conclusion: From these findings, it is reasonable that patients with dandruff may benefit from applying specific antifungal shampoo although results may vary with microbial species, time of contact and shampoo formulation components. Abstract : Filter paper shampoo washing experiment with different species of Malassezia or Staphylococcus and different anti‐dandruff shampoos. Résumé: OBJECTIFS: Les pellicules sont une affection cutanée complexe caractérisée par des démangeaisons et une desquamation du cuir chevelu. Elles sont principalement attribuées à une colonisation excessive par des levures du genre Malassezia telles que Malassezia globosa et Malassezia restricta. Certaines études suggèrent également que des bactéries comme les staphylocoques sont impliquées dans la pathogenèse des pellicules. Nous désirions évaluer l'efficacité des traitements antipelliculaires en déterminant l'efficacité des antifongiques actifs seuls ou dans des formulations commerciales de shampooing contre Malassezia et les bactéries du genre Staphylococcus. MÉTHODES: Les concentrations minimales inhibitrices de trois antifongiques présents dans des shampooings antipelliculaires (pyrithione de zinc, kétoconazole et ciclopirox) ainsi que l'hamamélan, extrait d'hamamélis, ont été évaluées contre des espèces commensales de Malassezia et Staphylococcus en utilisant des méthodes de microdilution en culture. Dans des expériences simulant l'exposition au shampooing et les conditions de lavage sur le cuir chevelu, nous avons également testé la capacité à inhiber la croissance microbienne des agents décrits ci‐dessus dans la formulation de shampooings (Head and Shoulders (H&S), Ketomed, Sebiprox, Erol Healthcare Hair Shampoo, respectivement) avec un produit générique trouvé dans le commerce. RÉSULTATS: Les shampooings Ketomed et H&S ont été les traitements les plus efficaces contre Malassezia dans des essais in vitro et dans des expériences de simulation de lavage. Le shampooing Erol Healthcare était moins efficace contre Malassezia in vitro car nécessitant un temps de contact plus long pour obtenir une inhibition de la croissance de certaines espèces. Sebiprox a montré une efficacité variable dans les expériences de lavage et de temps de contact alors que le shampooing générique était le moins efficace pour inhiber la croissance de Malassezia et Staphylococcus. CONCLUSION: Ces résultats suggèrent que les patients avec des pellicules peuvent raisonnablement retirer un bénéfice de l'utilisation d'un shampooing antifongique spécifique bien que les résultats puissent varier selon les espèces microbiennes, la durée du contact et des composants entrant dans la formulation du shampooing.